Phosphodiesterase-4 Inhibitors for Non-COPD Respiratory Diseases - Kawamatawong, Theerasuk (Frontiers in Pharmacology, 2021)
Selective phosphodiesterase (PDE) inhibitors are a class of nonsteroid anti-inflammatory drugs for treating chronic inflammatory diseases. Modulation of systemic and airway inflammation is their pivotal mechanism of action. Furthermore, PDE inhibitors modulate cough reflex and inhibit airway mucus secretion. Roflumilast, a selective PDE4 inhibitor, has been extensively studied for the efficacy and safety in chronic obstructive pulmonary disease (COPD) patients. According to the mechanisms of action, the potential roles of PDE inhibitors in treating chronic respiratory diseases including severe asthma, asthma-COPD overlap (ACO), noncystic fibrosis bronchiectasis, and chronic cough are discussed. Since roflumilast inhibits airway eosinophilia and neutrophilia in COPD patients, it reduces COPD exacerbations in the presence of chronic bronchitis in addition to baseline therapies. The clinical studies in asthma patients have shown the comparable efficacy of roflumilast to inhaled corticosteroids for improving lung function. However, the clinical trials of roflumilast in severe asthma have been limited. Although ACO is common and is also associated with poor outcomes, there is no clinical trial regarding its efficacy in patients with ACO despite a promising role in reducing COPD exacerbation. Since mucus hypersecretion is a result of neutrophil secretagogue in patients with chronic bronchitis, experimental studies have shown that PDE4s are regulators of the cystic fibrosis transmembrane conductance regulator (CFTR) in human airway epithelial cells. Besides, goblet cell hyperplasia is associated with an increased expression of PDE. Bronchiectasis and chronic bronchitis are considered neutrophilic airway diseases presenting with mucus hypersecretion. They commonly coexist and thus lead to severe disease. The role of roflumilast in noncystic fibrosis bronchiectasis is under investigation in clinical trials. Lastly, PDE inhibitors have been shown modulating cough from bronchodilation, suppressing transient receptors potential (TRP), and anti-inflammatory properties. Hence, there is the potential role of the drug in the management of unexplained cough. However, clinical trials for examining its antitussive efficacy are pivotal. In conclusion, selective PDE4 inhibitors may be potential treatment options for chronic respiratory diseases apart from COPD due to their promising mechanisms of action.